Organizational Justice in Administrative Thought: A Field Study at the National Centers for the Formation of Local Authority Personnel (CNFPCL) - BEZIEZ, Djoulanour; LOUKIA, Hachemi (Journal of Human Sciences, 2025)
This exploratory study was conducted as part of a doctoral dissertation titled "The Relationship between Organizational Justice and Organizational Citizenship Behavior," through a field investigation at the National Centers for the Formation of Local Government Employees. The aim was to assess employees’ perceptions of organizational justice across its three dimensions—distributive, procedural, and interactional—and to explore the influence of selected demographic factors on these perceptions. The research sample consisted of employees from the five national centers, chosen to ensure a diverse and representative dataset. Data were gathered primarily via a questionnaire and analyzed using SPSS software. The results revealed a moderate level of perceived organizational justice among the employees. Moreover, no statistically significant differences were observed in justice perceptions based on demographic characteristics.